Identifying vulnerable population in urban heat island: a literature review - Nurfatehar Ramly,; Mohd Rohaizat Hassan,; Mohd Hasni Jaafar,; Rohaida Ismail,; Zaleha Isa,; Rozita Hod, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The term "urban heat island" refers to a phenomenon that occurs when temperatures in urban areas are higher than those in the areas that surround them (suburban area). The urban heat island phenomenon can result in increase of energy consumption, increase of air pollution, decrease of water quality, and increase of greenhouse gas emissions, all of which have the potential to negatively impact people in a variety of ways. In this review we identified certain groups such as elderly, children, woman, pregnant woman, single person, and minority communities, who are living in dense area or in high rise building, low education level, low income, work in outdoor environment and had pre-existing illnesses may face health issues or insufficient resources to cope with the heat in urban area. There were more susceptible to heat-related illnesses and mortality, particularly during extreme heat events. Recognising these vulnerable populations is crucial to develop effective strategies to mitigate the effects of urban heat islands and protect them. This can aid policy makers and urban planners to implement targeted interventions to address these issues.